A Rare Case of Adult Post Traumatic Diaphragmatic Hernia - Manohar, Dr. Dharbind Kumar Jha, Dr. S.K Mohapatra, Dr. A.K Behera, Dr. Sunil Kumar Neti, Dr. Das Birendra (International Journal of Innovative Research in Medical Science, 2017)
Congenital diaphragmatic hernia (CDH) is a defect of the diaphragm associated with herniation of abdominal viscera into the chest cavity. We are going to report a case of post traumatic adult diaphragmatic hernia in a 45 yr female who presented with complain of severe vomiting and pain in left side of upper abdomen for 7 days with scaphoid abdomen, dull note on percussion and decrease breath sound on left side of chest. X ray and ultrasonography revealed herniation of stomach into left hemi thorax and mediastinal shift to right without significant deviation of trachea. CT scan confirmed the diagnosis and then exploratory laparotomy followed by decompression of stomach was done and the herniated stomach was repositioned in abdominal cavity. Chest tube was given in 6th ICS under supervision before the diaphragmatic defect was closed using prolene 1-0 and a prolene mesh was put over the defect and fixed. Gastrojejunostomy was done as the pyloric part of stomach was found to be fibrosed and stenosed. Post operatively the patient recovered well.